The future of surgical aortic valve replacement and the role of sutureless technology - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2018)
Aortic valve stenosis has become the most frequent type of valve disease in worldwide. Surgical aortic valve replacement is still the gold standard therapy. More recently transcatheter aortic valve implantation has been demonstrated to be not inferior in patients with high and intermediate risk patients. Sutureless aortic valves were designed to simplify the surgical aortic valve replacement. With the aid of this new technology, the invasiveness of surgery can be reduced with potential improvements in outcome.
Keywords: Aortic valve stenosis; Bioprosthesis; Transcatheter aortic valve replacement; RIGHT ANTERIOR MINITHORACOTOMY; HIGH-RISK PATIENTS; HEART-VALVE; CONDUCTION DISORDERS; CONVENTIONAL SURGERY; PERCEVAL VALVE; SINGLE-CENTER; PILOT TRIAL; FOLLOW-UP; TRANSCATHETER